Estimativas de parâmetros genéticos e a variabilidade em procedências e progênies de Handroanthus vellosoi - Batista, Camila Moreira [UNESP]; Freitas, Miguel Luiz Menezes; Moraes, Marcela Aparecida De [UNESP]; Zanatto, Antonio Carlos Scatena; Santos, Pedro César Dos [UNESP]; Zanata, Marcelo; Moraes, Mario Luiz Teixeira de [UNESP]; Sebbenn, Alexandre Magno (Embrapa Florestas, 2012)
The present study aimed at estimating genetic parameters and variability among and within provenances for silvicultural traits of Handroanthus vellosoi (Toledo) Mattos, in provenances and progenies test stands, located at the Luiz Antônio Experimental Station (São Paulo State, Brazil). The test was established in the compact family block design, with two provenances (allocated in the plots), siz replicates and sub-linear plots of five plants, totalizing 35 progenies. Diameter at breast (DBH), plant height, cylindrical volume, stem form and survival at 24 years of age were evaluated. Significant differences among the provenances were observed only to the trait stem form. The analysis of deviance showed significant differences among progenies for the joint analysis of the provenances (experimental population), suggesting that the population has high genetic variation and indicating the possibility of genetic improvement by selection of the best progrnies. Heritability estimates in individual and family level ranged from low to moderate (26% for DBH, 32% for plant height, 24% for cylindrical volume, 27% for form and 36% for survival), confirming the possibility of genetic improvement by selection and that the provenances have potential to respond to the pressure of natural selection.

O presente estudo objetivou estimar parâmetros genéticos e a variabilidade entre o dentro de procedências, para caracteres silviculturais em um teste de procedências e progênies de Handroanthus vellosoi (Toledo) Mattos estabelecido na Estação Experimental de Luiz Antônio (SP). O teste foi instalado no delineamento experimental de blocos de famílias compactas, com duas procedências (alocadas nas parcelas), seis repetições e sub-parcelas lineares de cinco plantas, totalizando 35 progênies. O ensaio foi mensurado para os caracteres diâmetro à altura do peito, altura da planta, volume cilíndrico, forma do fuste e sobrevivência aos 24 anos de idade. Diferenças significativas entre procedências foram observadas apenas para o caráter forma do fuste. Pela análise de deviance foram detectadas diferenças significativas para o efeito de progênies para análise conjunta das procedências (população experimental), sugerindo que esta tem alta variação genética e indicando possibilidade de melhoramento genético pela seleção das melhores progênies. A estimativa de herdabilidade em nível individual e média de progênies variaram de baixa a moderada (26% para DAP, 32% para altura, 24% para volume cilíndrico, 27% para forma do fuste e 46% para sobrevivência), confirmando a possibilidade de melhoramento genético por seleção e que as procedências tem potencial para responder à pressão de seleção natural.
Estimates of genetic parameters and variability in provenances and progeny of Handroanthus vellosoi
Keywords: Ex situ conservation; Tropical tree species; Population genetics; Quantitative genetics; Conservação ex situ; Espécies arbóreas tropicais; Genética de populações; Genética quantitativa